Demanded competencies of the entry-level position in the restaurant industry: employers' perspectives - Mohamad, Siti Fatimah; Lee, Lik Ying; Othman, Mohhidin; Ungku Zainal Abidin, Ungku Fatimah; Che Ishak, Farah Adibah; Abu Bakar, Ainul Zakiah (Human Resource Management Academic Research Society, 2020)
Researchers advocated that there are many issues of fresh graduates' competencies, including insufficient skills to meet the requirement as expected by the industry. The purpose of this study was to discover the entry-level competencies demanded by the restaurant employers towards fresh graduates. The dynamic workforce and the mismatch competencies claimed by employers are the issues that trigger education stakeholders, particularly in Malaysia. Responses were obtained from eight restaurant managers in Klang Valley, through a semi-structured interview. The data were then analyzed using thematic analysis. There were nine competencies emerged from this study, which reflect the entry-level competencies demanded by restaurant managers towards fresh graduates, namely: 1) attitude and behavior, 2) cognitive skill, 3) communication skill, 4) knowledge in the discipline area, 5) professionalism and work ethics, 6) technical skill, 7) teamwork, 8) leadership and 9) experience. It is anticipated that the findings will be able to fulfill the restaurant's needs by giving a clear picture of the essential competencies that need to be infused in the university's curriculum. Besides, both educators and fresh graduates will have an insight into the preparation for working in the restaurant industry.